Building with Jelly, or, Concrete as the Concretion of the Abstract - Alan Díaz Alva (Footprint)
In his recent book titled *Béton: arme de construction massive du capitalisme*, Marxist thinker Anselm Jappe presents a critique of the emergence and ongoing centrality of reinforced concrete as a hegemonic building material. In this slim volume, Jappe traces its historical trajectory, analysing the economic pressures propelling its hegemonic consolidation, examining the central role it played in political projects of various stripes, and critiquing the social, cultural, and environmental consequences of the latter. What is interesting and novel about his contribution, however, is the conceptual framework deployed for this purpose. Unlike most Marxist critiques of architecture which usually focus on questions of class or ideology, Jappe focuses on matter and abstraction. Value-form theory (and the tradition of German *Wertkritik* which Jappe is part of), reads Marx’s theory of value as a theory of the abstract domination of human life and social practice by the abstract forms set in motion by the capitalist mode of production.